Development of pollinium in Malaxis muscifera (Lindl.) Kuntze (Bangladesh Journal of Botany, 2011)
Anther primordium of Malaxis muscifera (Lindl.) Kuntze initiated as a homogenous mass of meristematic cells is surrounded by protoderm. Two thecae are oriented towards the labellum, each of them consisted of a mass of archesporial cells. The hypodermal layer of sporogenous cells divide periclinally to form an endothecial, a middle layer and a tapetum. Pollen mother cells formed different types of microspore tetrads. Each microspore divides mitotically resulting a generative and a vegetative cell. Degeneration of the sterile septum resulted four naked and clavate pollinia. Key words: Malaxis muscifera; Anther; Pollinium; Morphogenesis DOI: 10.3329/bjb.v39i2.7480 Bangladesh J. Bot. 39(2): 193-198, 2010 (December)